Legal Protection for Workers in Fixed-Term Employment Agreements (PKWT) in Regional-Owned Enterprises Regarding the Absence of Maternity Leave: A Human Rights Perspective in Relation to Law Number 6 of 2023 on Job Creation - Pepe Febianti; Ade Maman Suherman; Tri Setiady (Jurnal Indonesia Sosial Sains, 2024)
The absence of maternity leave for female workers in Fixed-Term Employment Agreements (PKWT) in regionally-owned companies is an important issue related to legal protection and human rights. This study aims to examine legal protection and relevant regulations based on Law No. 6 of 2023 on Job Creation, with specific objectives to: 1) analyze the extent of compliance of regionally-owned companies with labor laws concerning maternity leave; and 2) identify and address the factors contributing to the non-implementation of these rights. Using a normative juridical approach, this study identifies discrimination against female workers, who by nature require more protection in terms of reproduction. The results show that the elimination of maternity leave rights violates Article 153 paragraph (1) of Law Number 6 of 2023, which prohibits termination of employment for reasons of pregnancy or childbirth. The Labor Law provides special rights such as maternity leave to female workers. In conclusion, the company's policy of eliminating this right is against the principle of non-discrimination in human rights. It is recommended that companies comply with labor regulations to ensure the welfare of female workers.